(untitled) (The Review of Diabetic Studies, 2025)
Background: Post-surgery wound infections complication becoming more common and global trend due to multi drug resistant bacteria. The problem is causative agent changing their strategy continuously toward antibiotic, so the antibiotic cannot manage the treatment. Therefore, we tried for alternative treatment or using substance has antibacterial activity. Subsequently we used extracts from different part of Pomegranate. However, there hasn’t been much published study employing using Pomegranate extract for surgical wound infections. Study Design: A prospective study was conducted on 100 post-surgical patients at Mihrabani Hospital Private in Erbil Province, Kurdistan Region, Iraq, from September 2024 to April 2025. Swabs were collected from these patients. Out of the 100 samples, 80 (80%) yielded positive cultures, while 20 (20%) showed negative results. Gram-positive bacteria accounted for 30 (30%) of the positive culture isolates, which were not included in the study. The remaining 50 percent consisted of gram-negative bacteria. Among the patients, there were 30 females (60%) and 20 males (40%), with ages ranging from 20 to 80 years. Researchers employed various solvents at multiple concentrations to evaluate their effectiveness against the isolated bacteria. Results: percent study investigates 50-gram negative bacteria isolated from post-surgical infections using VITEK 2 system. Other gram-positive bacterial isolates excluded from the study. Cassette within 26 antibiotics assessed against gram negative bacteria. The study found most frequent isolates coursing infection was Escherichia coli (E. coli) and Pseudomonas aeruginosa. Various solvent used for extraction of (PP) pomegranates peel, (PC) pomegranates core, (PPC) peel and core pomegranate tested against isolated bacteria. Punica granatum contains ellagitannins, gallic acid, and phenolic acids that are rich in tannins and exhibit antibacterial properties. This study demonstrated the sizes of the inhibitory zones for different types of bacterial infections caused by each extract. We evaluated the effectiveness of these compounds in killing bacteria by using methanol, ethanol, and distilled water (DW) extracts at concentrations of 100%, 75%, 50%, and 25%. Conclusion: In the present study many etiological agents have been isolated causing surgical infection with their susceptibility pattern. P. granatum extracts used with various solvent. We found most effective solvent was methanol followed by ethanol. While, less effective solvent was water.